Climate suitability for tourism in South Africa. Issue 6 (3rd June 2017) - Fitchett, Jennifer M; Robinson, Dean; Hoogendoorn, Gijsbert
ABSTRACT: Tourism Climate Indices (TCIs) have been used extensively in the global North to quantify the climatic suitability of tourist destinations. TCIs have very seldom been applied in the global South. This gap in the literature is significant, due to the considerable growth that tourism sectors in the global South have experienced over recent decades. Moreover, many of these countries seldom have the infrastructure to modify indoor climates and effectively mitigate against poor weather. We present TCI results for 18 tourist destinations across South Africa. With mean annual TCI scores for the period 1995–2015 spanning 76.5 for Port Nolloth to 93 for the Pilansberg, the comparatively favourable climatic conditions in South Africa relative to much of Europe and North America is confirmed. There is distinct seasonality in TCI scores for the majority of study locations, yet the dichotomy between the South African summer and rainfall zones ensure a net balance in climatic suitability countrywide year-round. Time trends in TCI scores over recent decades indicate non-significant change for the majority of locations, and all significant trends indicate slight improvements in the climatic suitability for tourism. These results present a promising outlook of sustained climatic suitability of the region for tourism.